The boundaries of monotheism : interdisciplinary explorations into the foundations of western monotheism - Haardt, Maaike de, 1954-; Korte, Anne-Marie, 1957- (Studies in Theology and Religion, 2009)
What is the significance of monotheism in modern western culture, taking into account both its problematic and promising aspects? Biblical texts and the biblical faith traditions bear a continuous, polemical tension between exclusive and inclusive perceptions and interpretations of monotheism. Western monotheism proves itself to be multi-significant and heterogeneous, producing boundary-setting as well as boundary-crossing tendencies, is the common thesis of the authors of this book, who have been collectively debating this theme for two years in an interdisciplinary scholarly setting. Their contributions range from the fields of biblical and religious studies, history and philosophy of religion, systematic theology, to gender studies in theology and religion.The authors also explain the particular contribution of their own theological discipline to these debates.